The Membrane Axis of Alzheimer's Nanomedicine. Issue 1 (8th December 2020) - Li, Yuhuan; Tang, Huayuan; Andrikopoulos, Nicholas; Javed, Ibrahim; Cecchetto, Luca; Nandakumar, Aparna; Kakinen, Aleksandr; Davis, Thomas P.; Ding, Feng; Ke, Pu Chun
Abstract : Alzheimer's disease (AD) is a major neurological disorder impairing its carrier's cognitive function, memory, and lifespan. While the development of AD nanomedicine is still nascent, the field is evolving into a new scientific frontier driven by the diverse physicochemical properties and theranostic potential of nanomaterials and nanocomposites. Characteristic to the AD pathology is the deposition of amyloid plaques and tangles of amyloid beta (Aβ) and tau, whose aggregation kinetics may be curbed by nanoparticle inhibitors via sequence‐specific targeting or nonspecific interactions with the amyloidogenic proteins. As literature implicates cell membrane as a culprit in AD pathogenesis, herein, the membrane axis of AD nanomedicine is summarized and a new rationale that the field development may greatly benefit from harnessing our existing knowledge of Aβ‐membrane interaction, nanoparticle–membrane interaction, and Aβ–nanoparticle interaction is presented. Abstract : The development of AD nanomedicine, an emerging frontier in advanced nanobiomedical research, can benefit from the accumulating knowledge of Aβ–cell membrane, nanoparticle–cell membrane, and Aβ–nanoparticle interactions.